Bitcoin: meio de pagamento ou investimento - Silveira, Diego Barros (2023)
The purpose of this research is to analyze the performance of Bitcoin since its creation in order to determine whether this cryptocurrency is better suited as a method of payment or investment. Being, for this, treated the whole history of the currency from the first exchanges to the emergence of digital currencies, the emergence of Bitcoin and blockchain technology and its growth over the years, the comparison with CBDCs that are in development, the benefits of use of Bitcoin as a method of payment and investment. As a method of payment, Bitcoin makes it possible to carry out international transactions with very low fees and as a method of investment, the high level of volatility presented in comparison to two shares of the Brazilian stock exchange, demonstrates that investing in the currency poses a high risk